Identification, classification, and transcription profiles of the B-type response regulator family in pear. - Junbei Ni; Songling Bai; Ling Gao; Minjie Qian; Linbing Zhong; Yuanwen Teng (PLoS ONE, 2017)
Type-B response regulators (B-RRs) are transcription factors that function in the final step of two-component signaling systems. In model plants, B-RRs have been shown to play important roles in cytokinin signal transduction. However, the functions of B-RRs in pear have not been well studied. In this report, we conducted a genome-wide analysis and identified 11 putative genes encoding B-PpRR proteins based on the published genome sequence of Pyrus bretschneideri. A phylogenetic tree of the B-PpRR family was constructed, and the motif distribution, chromosome localization, and gene structure of B-PpRR family genes were determined. Gene transcript profiles, which were determined from transcriptome data, indicated that B-PpRR genes potentially function during pear fruit development, bud dormancy, and light/hormone-induced anthocyanin accumulation. Treatment of the fruitlets of 'Cuiguan' pear (Pyrus pyrifolia), which never accumulates anthocyanin, with the cytokinin N-(2-chloro-4-pyridyl)- N'-phenylurea (CPPU) clearly induced anthocyanin accumulation. Anthocyanins accumulated in the skin of fruitlets by 16 days after CPPU treatment, along with the significant activation of most anthocyanin biosynthetic genes. Analyses of B-PpRR transcript levels suggested that B-PpRR genes mediated this accumulation of anthocyanins. These findings enrich our understanding of the function of B-PpRR genes in the physiological processes of pear.